2021
DOI: 10.3390/pathogens10111370
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of COVID-19-Associated Pulmonary Aspergillosis in Intensive Care Unit—A Monocentric Retrospective Observational Study

Abstract: Coronavirus disease 2019 (COVID-19)-associated pulmonary aspergillosis (CAPA) is an increasingly recognized complication of COVID-19 and is associated with significant over-mortality. We performed a retrospective monocentric study in patients admitted to the intensive care unit (ICU) for respiratory insufficiency due to COVID-19 from March to December 2020, in order to evaluate the incidence of CAPA and the associated risk factors. We also analysed the diagnostic approach used in our medical centre for CAPA di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Although the prevalence of CAPA in our ICU‐admitted patients (6.04%) is similar to other works 27 and is consistent with studies in our setting 31 and autopsy studies, 32 some other authors have noted a higher prevalence, 4 , 12 , 28 , 33 up to 30%. 34 These differences could be related to regional variations in incidence.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although the prevalence of CAPA in our ICU‐admitted patients (6.04%) is similar to other works 27 and is consistent with studies in our setting 31 and autopsy studies, 32 some other authors have noted a higher prevalence, 4 , 12 , 28 , 33 up to 30%. 34 These differences could be related to regional variations in incidence.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have identified risk factors for CAPA, including age, prior respiratory diseases, chronic renal failure, chronic corticosteroid use, neutropenia, COVID‐19 severity and treatment of the COVID‐19 episode with corticosteroid or tocilizumab 4,13,26‐28 . In the present study, we could validate most of these factors.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Systemic fungal superinfections can negatively impact the prognosis and subsequently increase the mortality rate among patients with COVID-19. Certain risk factors ascribed to the development of CAPA, include age, prior respiratory diseases, chronic renal failure, long-term use of corticosteroid, neutropenia, COVID-19 severity, and treatment of COVID-19 patient with corticosteroid or tocilizumab [ 12 , 13 , 23 , 24 ]. In the present study, 17 isolates were recovered from cases considered to be CAPA.…”
Section: Discussionmentioning
confidence: 99%
“…The overlapping respiratory manifestations complicate the treatment of COVID-19. Prolonged hospitalization period and potentially required mechanical ventilation along with lymphopenia, leukopenia, and systemic hyperinflammatory reaction facilitates the growth of fungi in COVID-19 patients ( Arastehfar et al, 2020a ; Amin et al, 2021 ; Baddley et al, 2021 ; Gregoire et al, 2021 ). In addition, World Health Organization (WHO) COVID-19 treatment guideline recommend empirically prescribed broad-spectrum antibiotics to treat possible bacterial co-infections, but only in severe COVID-19 patients ( World Health Organization, 2021 ).…”
Section: Introductionmentioning
confidence: 99%